Research Productivity of the University of Jaffna (2010- 2024) after the Civil war of Sri Lanka: A Scientometric Analysis based on Web of Science database. - Poologanathan, P. (Sri Lanka Library Association, 2025)
This study analyzes the research productivity of the University of Jaffna from 2010 to 2024, a period following the end of Sri Lanka's civil war. University of Jaffna was established in 1974 in the Northern region of Sri Lanka and experienced substantial disruptions due to the civil conflict that lasted from 1984 to 2009. Totally, number of 739 publications by the University of Jaffna was indexed with 15,946 Citations in the Web of Science database from 1989-2024. However, our analysis, focusing on post war growth, covers 616 publications indexed in the Web of Science database from 2010–2024. Using HistCite, Biblioshiny, VOSviewer, and M.S.Excel, this scientometric study assesses key research indicators, including authorship patterns, yearly publication, citation metrics, keyword distributions, highly productive authors and international collaborations. In this study, findings show that the University of Jaffna produced 616 publications, garnering a total of 12,232 citations with an overall h-index of 46. Publication output peaked in 2022 with 85 records (14%), and engineering emerged as the most represented discipline with 105 publications (17%). The most productive author was S. N. Surendran, contributing 55 publications (9%), while K. Vignarooban recorded the highest citation impact with 2,495 citations (20%). The study summarizes that after the civil war of Sri Lanka, research productivity of University of Jaffna increased due to international collaborations and technological advancements. The findings offer valuable insights for governments, academic institutions, librarians, and researchers, contributing to an understanding of regional scholarly growth and supporting future academic planning and development.
Keywords: Civil war; Post-war; University of Jaffna; Research Productivity; Sri Lanka; Scientometric analysis